Analysis of trnL- trnL- trnF Intergenic Spacer and matK Sequences Combined with Morphological Observations Showed Pucuk Seminyak from Riau is Champereia manillana var. manillana Merr.: trnL-trnL-trnF Intergenic Spacer and matK on Pucuk Seminyak - Roslim, Dewi Indriyani; Herman; Budiono, Deanne Yoshe Fidela; Cahyati, Isa Endar; Lestari, Wahyu; Novita, Linda; Priyadi, Arief (Journal of Tropical Life Science, 2024)
A taxonomic status of Pucuk Seminyak plant is still unclear. This plant has a fruit like Melinjo (Gnetum gnemon) fruit and is often classified as a member of Gnetaceae family. This study aims to determine the taxonomic status of Pucuk Seminyak from Riau using trnL-trnL-trnF intergenic spacer (IGS) and matK sequences. Methods included leaf samples from three individuals collected from the Kampar Regency, Riau Province, total DNA extraction, electrophoresis, polymerase chain reaction (PCR), and data analysis. The results showed that the trnL-trnL-trnF IGS DNA sequences from the three samples of Pucuk Seminyak were obtained 937 bp length, while the matK had a size of 775 bp. These sequences have been registered in GenBank with registration numbers OQ174512, OQ174513, and OQ174514 for trnL-trnL-trnF IGS, and OQ174525, OQ174526, and OQ174527 for matK. The highest similarity was found between Pucuk Seminyak and Champereia manillana with an identity value of 99.67% based on trnL-trnL-trnF IGS and 99.74% based on matK. BLASTn analysis by default settings and organism Champereia (taxid: 50116) resulted in hits on the Champereia genus of the Opiliaceae. Further phylogenetic analysis placed the study objects in the Champereia clade (bootstrap support 49 for trnL-trnL-trnF, 68 for matK, and 71 for concatenated sequences). Lastly, identification by morphological characters also confirmed that the specimen agreed with the description and identification key for C. manillana. The species is classified into two varieties: var. longistaminea and var. manillana. The former was distributed in Southwest China, and the latter was distributed in Malesia to India. Furthermore, the phylogenetic analysis separated the two varieties into different clades. Therefore, it can be concluded that our specimen of Pucuk Seminyak is identified as C. manillana var. manillana Merr. (Opiliaceae).